Digging into the digital divide: Workers' exposure to digitalization and its consequences for individual employment - Sabrina Genz; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2021)
While numerous studies have analyzed the aggregate employment effects of digital technologies, this paper focuses on the employment development of individual workers exposed to digitalization. We use a unique linked employer-employee data set for Germany and a direct measure of the first-time introduction of cutting-edge digitalization technologies in establishments between 2011 and 2016. Applying a matching approach, we compare workers in establishments investing in digital technologies with similar employees in establishments that do not make such an investment. We find that the employment stability of incumbent workers is lower in investing than non-investing establishments, but most displaced workers easily find jobs in other firms, and differences in days in unemployment are small. We also document substantial heterogeneities in the employment effects across skill groups, occupational tasks performed, and gender. Employment reactions to digitalization are most pronounced for both low- and high-skilled workers, for workers with non-routine tasks, and for female workers. Our results underline the importance of tackling the impending digital divide among different groups of workers.
Keywords: J21; J63; O33; 330; digitalization; employment; separations; skills; tasks